Manushe: 25 Years of Empowering Romani Women’s Voices - Laburdová, Claudie (Romano džaniben, 2025)
This article presents the development and activities of the Romani women’s group Manushe, which has been working for more than 25 years to empower Romani women in Czech society through education, community work, and civic participation. The text traces the evolution of the issues the group has addressed—from promoting self-confidence and education, through professional advancement and political participation, to current activities focused on preventing domestic and gender-based violence. Special attention is given to a study conducted in 2024 among 500 Romani women, which, thanks to the trust built within the communities, yielded valuable insights into the prevalence of violence, its perception, and strategies for addressing it. The results show that domestic violence is a serious and often long-term problem that needs to be discussed openly, while also confirming the key role of community initiatives in identifying and addressing it.